Philippines sanitaion sourcebook and decision aid : (The World Bank, 2005)
The Sanitation Sourcebook, focusing the information about the low-cost sanitation technology options, aims to stimulate effective demand for sanitation services by presenting tools for strategic decision-making around a wider range of more affordable sanitation options. It also hopes to stimulate informed investment decisions by local governments to ensure more sustainable outcomes. Thus, it features environment-friendly and affordable decentralized solutions.